Establishment and development of legislative regulation of industrial designs as objects of intellectual property law in Ukraine - Батько, Ірина; Batko, Iryna (Видавництво Львівської політехніки, 2023)
Висвітлено низку актуальних питань становлення та розвитку правової охорони промислових зразків. Автором проаналізовано правове регулювання досліджуваних відносин та визначено основні етапи його розвитку. Метою цієї статті є правовий аналіз положень законодавства України щодо становлення та розвитку правового регулювання промислових зразків, визначення дискусійних законодавчих положень та висловлення пропозицій щодо вдосконалення відповідного правового регулювання. Методи дослідження. Використано системний метод (при з'ясуванні місця промислового зразка в системі об’єктів права промислової власності), порівняльний метод (при порівнянні етапів розвитку національного законодавства). Історичний метод застосовувався для дослідження становлення та розвиток законодавства у сфері промислової власності у хронологічній послідовності, починаючи від 1991 р. і закінчуючи сьогоденням; формально-юридичний метод – для комплексної характеристики законодавства України щодо промислових зразків. Метод наукового тлумачення права – використовувався для з'ясування змісту відповідних правових норм. Висновки. Доведено, що становлення законодавства України, яке регулює відносини щодо виникнення прав на промислові зразки, їх здійснення та захист, відбувалося у кілька етапів. Встановлено, що перший етап тривав протягом 1991–2003 рр. (відбулося започаткування вітчизняного законодавства щодо промислової власності), другий етап тривав протягом 2003–2014 рр., під час якого відбувся розвиток національного законодавства у цій сфері, третій етап розпочався у 2014 р. і триває до тепер (має місце гармонізація національного законодавства у сфері промислової власності з правом ЄС). Доведено, що після здобуття Україною незалежності в Україні було практично відсутнє правове регулювання промислових зразків. Встановлено, що єдиним нормативним актом, який містив хоча б кілька норм щодо промислових зразків, був Цивільного кодексу України УРСР. Доведено, що першим нормативним актом, який врегульовував відносини щодо промислових зразків, було Тимчасове положення про правову охорону об'єктів промислової власності та раціоналізаторських пропозицій в Україні, яке відіграло важливу роль у наступному становленні законодавства про промислові зразки. Обґрунтовано, що прийняття Закону України «Про охорону прав на промислові зразки» від 15.12.1993 р. було наступним важливим кроком у становленні правового регулювання досліджуваних відносин, оскільки цей закон дуже ґрунтовно унормував відносини, що виникають у зв'язку з набуттям і здійсненням прав на промислові зразки. Обґрунтовано, що другий етап у становленні і розвитку законодавства про промислові зразки був зумовлений прийняттям Цивільного кодексу України у 2003 р., у зв'язку з цим було суттєво вдосконалено багато законодавчих положень, які в подальшому діяли близько 20 років. Встановлено, що основні законодавчі новації (2003) були наступними: змінено умови патентоспроможності, удосконалено зміст новизни промислового зразка, змінено порядок проведення експертизи заявки, вдосконалено порядок публікації про видачу патенту та реєстрацію патенту, змінено порядок оскарження рішення патентного відомства за заявкою на промисловий зразок, удосконалено правові норми щодо використання промислового зразка, щодо припинення дії патенту, щодо захисту прав на промислові зразки. Встановлено, що третій етап щодо розвитку законодавства про промислові зразки розпочався у 2014 р. (підписання Угоди про асоціацію між Україною та ЄС) і триває по сьогодні. Встановлено, що Угода про асоціацію між Україною та ЄС містить великий за обсягом Розділ про інтелектуальну власність, кілька статей присвячені саме промисловим зразкам (ст. 212 – 218). Обґрунтовано, що ці статті заклали фундамент майбутнього реформування законодавства України про промислові зразки, яке відбулося лише у 2020 р. Доведено, що станом на сьогодні законодавство України щодо промислової власності загалом, і щодо промислових зразків зокрема, є максимально наближеним до стандартів ЄС у цій сфері, і здатне належно врегульовувати відносини.

The article analyses the coverage of topical issues of formation and development of legal protection of industrial designs. The author analysed the legal regulation of the studied relations and identified the main stages of its development. The purpose of this article is a legal analysis of the provisions of the legislation of Ukraine regarding the formation and development of the legal regulation of industrial designs, the definition of debatable legislative provisions and the expression of proposals for the improvement of the relevant legal regulation. Research methods. There were used a systematic method (when clarifying the place of an industrial design in the system of objects of industrial property rights), a comparative method (when comparing the stages of development of national legislation). The historical method was used to study the formation and development of legislation in the field of industrial property in a chronological sequence, starting from 1991 and ending with the present; formal-legal method - for a comprehensive characterization of the legislation of Ukraine regarding industrial designs. The method of scientific interpretation of law was used to clarify the content of relevant legal norms. Conclusions. It has been proven that the formation of the legislation of Ukraine, which regulates relations regarding the emergence of rights to industrial designs, their implementation and protection, took place in several stages. It was established that the first stage lasted during 1991–2003 (the initiation of domestic legislation on industrial property took place), the second stage lasted during 2003–2014, during which the development of national legislation in this area took place, the third stage began in 2014. and continues until now (harmonization of national legislation in the field of industrial property with EU law is taking place). It has been proven that after Ukraine gained independence, there was practically no legal regulation of industrial designs in Ukraine. It was established that the only normative act that contained at least a few norms regarding industrial designs was the Civil Code of Ukraine of the Ukrainian SSR. It has been proven that the first regulatory act that regulated relations regarding industrial designs was the Temporary Provision on Legal Protection of Industrial Property Objects and Innovative Proposals in Ukraine, which played an important role in the subsequent development of legislation on industrial designs. It is substantiated that the adoption of the Law of Ukraine "On the Protection of Rights to Industrial Designs" dated 12/15/1993 was the next important step in the establishment of legal regulation of the studied relations, since this law very thoroughly normalized the relations arising in connection with the acquisition and exercise of rights on industrial samples. It is substantiated that the second stage in the formation and development of the legislation on industrial designs was determined by the adoption of the Civil Code of Ukraine in 2003, in connection with this, many legislative provisions were significantly improved, which subsequently operated for about 20 years. It was established that the main legislative innovations (2003) were as follows: the conditions of patentability were changed, the novelty content of an industrial design was improved, the procedure for conducting an examination of an application was changed, the procedure for the publication of the grant of a patent and patent registration was improved, the procedure for appealing the decision of the patent office on an application for an industrial design was changed, the legal norms regarding the use of an industrial design, the termination of patent validity, and the protection of rights to industrial designs have been improved. It was established that the third stage regarding the development of legislation on industrial designs began in 2014 (signing of the Association Agreement between Ukraine and the EU) and continues to this day. It has been established that the Association Agreement between Ukraine and the EU contains a large Section on intellectual property, several articles are devoted to industrial designs (Articles 212 - 218). It is substantiated that these articles laid the foundation for the future reform of the legislation of Ukraine on industrial designs, which took place only in 2020. It has been proven that, as of today, the legislation of Ukraine regarding industrial property in general, and regarding industrial designs in particular, is as close as possible to EU standards in this area, and is able to properly regulate relations.
Становлення та розвиток законодавчого регулювання промислових зразків як об’єктів інтелектуальної власності в Україні
Keywords: промисловий зразок; інтелектуальна власність; патент; свідоцтво; умови патентоздатності; критерії охороноздатності; стандарти ЄС; industrial design; intellectual property; patent; certificate; patentability conditions; protectionability criteria; EU standards; 347.773.3